Incidence of Root Knot Nematodes of Cucumber in high plastic tunnels at Quetta and its Management in Greenhouse Conditions (Plant Bulletin, 2025)
Cucumber (Cucumis sativus L.) is one of the most important vegetables in Pakistan and worldwide and being affected with root knot nematode in high plastic tunnels. The study was conducted to survey high plastic tunnels at Quetta, Balochistan Pakistan and samples have been disease samples have been collected. The maximum disease incidence in the high plastic tunnels was recorded 30% at Baleli area and minimum 10% at Sariab and Nausar areas. Management experiment was conducted to evaluate the impact of various nematicides on the growth, and physiological traits of cucumber plants. Treatment includes chemicals viz., Carbofuran, Fostiazate, Fluopyrum, Oxamyl, and Cadusafos, compared against an untreated control group of cucumber pants. Carbofuran consistently produced the highest values across all parameters, including number of fruits per plant (7.10), fruit weight (28.80 g), fruit length (13.2cm), seed number per fruit (40.0), number of leaves (19.2), plant height (47.8 cm), fresh shoot weight (78.8 g), fresh root weight (23.80 g), dry shoot weight (46.5 g), and dry root weight (14.0 g). Fostiazate and Fluopyrum followed in performance, showing significantly better results than Oxamyl, Cadusafos, and the control for most parameters. Oxamyl and Cadusafos displayed moderate improvements over the control on various parameters. The untreated control consistently recorded the lowest values in growth and yield characteristics. Notably, Carbofuran also induced the lowest number of root galls (6.0), significantly below other treatments, with Cudusaps showing the highest gall count (28.0). These results demonstrate that chemical treatments of Carbofuran followed by Fostiazate substantially enhance cucumber growth and are recommended for management of root knot in green house condition